Sally's cookie addiction : irresistible cookies, bars, shortbread, and more from the creator of Sally's baking addiction - McKenney, Sally (Race Point Publishing, 2017)
A collection of recipes for cookies, cookie bars, cookie dough dips, slice-and-bakes, and no-bakes includes such options as brown butter snickerdoodles, pinwheel cookies, fairy meringues, jam shortbread bars, and chocolate hazelnut thumbprints.